The impact of COVID-19 on the psychiatric emergency departments of two Italian hospitals in Milan. (January 2022) - Cafaro, Rita; Piccoli, Eleonora; Ferrara, Luca; Russo, Stefania; Dragogna, Filippo; Viganò, Caterina; Mencacci, Claudio; Dell'Osso, Bernardo
HIGHLIGHTS: The SARS-CoV-2 pandemic has affected Italy from the end of February 2020. Emergency Departments were overloaded due to the high number of SARS-CoV-2 positive patients. Psychiatric evaluations in Emergency Departments suffered a reduction due to the pandemic. The type of patients requiring psychiatric evaluation changed due to the pandemic. ABSTRACT: During the first wave of the SARS-CoV-2 contagion in Italy, mental health care services continuity has been granted to the general population. Emergent and urgent conditions, however, are managed in collaboration with Emergency Departments (EDs). This collaboration may have suffered from the overload of the EDs due to the high number of SARS-CoV-2 positive patients. In this perspective, we analysed the possible impact of COVID-19 on the EDs accesses of psychiatric patients in two of the main hospitals of Milan, the "Luigi Sacco" Hospital and the "Fatebenefratelli" Hospital, comparing their admissions between the periods of March, April and May 2019 and 2020. We found a significant reduction in the number of evaluated patients in 2020 in both EDs. Emergency Medical Services (EMSs) brought a significant lower number of patients to the ED of Sacco Hospital during 2020, while this number increased for the ED of Fatebenefratelli Hospital, confirming the hypothesis that the overload of the Sacco Hospital ED significantly influenced the possibility to receive a psychiatric evaluation there. Moreover, we found a significant difference between diagnosis at discharge of the different samples.